Utilization of biochar for a process of methane dry reforming coupled with steam gasification under microwave heating. (10th November 2019) - Li, Longzhi; Chen, Jian; Wang, Sheng; Tan, Yongdong; Meng, Bo; Zou, Guifu; Wang, Fumao; Song, Zhanlong; Ma, Chunyuan
Abstract: A process of combining methane dry reforming and biochar steam gasification was conducted under microwave heating, using biochar as a catalyst in the reforming process and as a fuel in the gasification process. Through this process, biochar was efficiently utilized and the desired syngas production was obtained. The influences of various parameters consisting of heating mode, temperature, inlet gas composition and addition of metal component on methane conversion and the evolution of biochar remained mass ratio in the whole process of 4 h were focused on in this article. Besides, syngas yield and H2 /CO ratio achieved under different conditions were compared. Microwave heating was more capable of favoring this process than electric heating, which could promote methane conversion by 12.1% and increase the decline of remained mass ratio by 9.2% in the gasification process. Overall, the process initiated at 800 °C was more efficient than that initiated at the other temperature. The reforming process was optimized at an equable distribution of CH4 and CO2 . Nevertheless, the best reactivity in the first 60 min of gasification process was occurred on biochar obtained from the reforming process with CH4 /CO2 ratio of 1:1.5, featured by a reduction of remained mass ratio up to 16.1%. Compared with the use of pure biochar, the addition of Fe improved methane conversion by 3.6%, but also enhanced biochar gasification reactivity, with biochar remained mass ratio dropped to 51.9%. The maximized syngas yield was 93.2% in this paper, together with H2 /CO ratio at 0.98. Highlights: A process coupled methane reforming with steam gasification was proposed. The process was benefited from the utilization of microwave heating. A modest temperature of 800 °C was appropriate for the integrated process. Bioachar catalytic performance and its gasification reactivity were affected by the composition of inlet gas. The addition of Fe into biochar was proved be the most effective for this process.